(untitled) (Academia Science Repository, 2023)
This article attempts to substantiate the symbolic development of national character and morality by comparing it with symbiotic phenomena and processes in nature. Also discussed were the socio-philosophical aspects of the development of morality in relation to the national character in connection with the development of time, and the consequences of violating the symbol of national character and morality.